The Philippines as an Archipelagic and Maritime Nation: Interests, Challenges, and Perspectives - Mary Ann, Palma (2016)
The geographic nature of the Philippines as well as its numerous activities in relation to the sea, are integral to the identity of the country and critical in securing its maritime interests. These interests have a number of facets, which include the protection of national territorial integrity, marine resources, maritime industry and the marine environment, as well as the promotion of maritime safety and security. However, current national laws, policies, and programs suggest that the Philippines has not fully taken into account its unique archipelagic and maritime characteristics in addressing its concerns. The Philippines has been progressing more as a maritime nation rather than as an archipelagic nation, largely because of the difficulties in defining the limits of its national jurisdiction consistent with the provisions of the United Nations Convention on the Law of the Sea. This reality calls for a transformation in strategic thinking to develop a truly archipelagic and maritime approach for the Philippines—an approach which would embody both inward and outward looking perspectives in protecting the country’s interests and responding to various challenges.